Bringing the Romanian Theatre to American Universities: The Plays of Mona Chirilă at Arizona State University - ORLICH, Ileana Alexandra (Studia Universitatis Babeș-Bolyai Dramatica, 2018)
When talking about Romanian theatre staged abroad, in the United States and especially in Phoenix, Arizona, it is impossible not to mention the extremely talented director Mona Marian (Chirilă). She started her theatrical journey at Arizona State University in the Romanian Studies program at the Department of Languages, due to her encounter with prof. Ileana Orlich, after a performance at the National Theatre in Cluj-Napoca in 2000, where a beautiful friendship started. An important number of poetical and most creative performances toured to the United States, where the Romanian diaspora audience and the American student audience could participate to these unforgettable shows.